Economical high-nitrogen easy-to-form austenitic stainless steel and manufacturing method thereof

Through alloying design and process optimization in austenitic stainless steel, the problem of cracking of nickel-segmented austenitic at large deformation positions is solved, and the application of high-nitrogen easy-to-form austenitic stainless steel is realized, with 304-level corrosion resistance and excellent The swelling performance has successfully replaced 304 stainless steel for use in the fields of dishwasher door panels and range hoods.

CN119194252AActive Publication Date: 2024-12-27福建青拓特钢技术研究有限公司

Patent Information

Application Number
CN202411300516.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing nickel-dead austenitic stainless steel has limited application in dry areas and interior decoration fields, and is prone to cracking in large deformation locations, making it difficult to replace the application of 304 stainless steel in the fields of dishwasher door panels and range hoods. .

Method used

It adopts economical high-nitrogen easy-to-form austenitic stainless steel, with chemical components including C, Si, Mn, Cr, Ni, Cu, N and other elements. Through alloying design and process optimization, the yield strength, elongation and corrosion resistance are controlled. Ensure that the product has excellent swelling performance on the basis of high nitrogen and high strength, and solves the problem of molding and cracking.

Benefits of technology

It has achieved low cost and corrosion resistance of 304 stainless steel grade, yield strength exceeds 400MPa, elongation exceeds 55%, and pitting potential exceeds 300mV. It has successfully replaced 304 stainless steel for products such as dishwasher door panels and range hoods, and solved the problem of The problem of forming cracking is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194252A_ABST
    Figure CN119194252A_ABST
Patent Text Reader

Abstract

The economical high-nitrogen easy-to-form austenitic stainless steel comprises the following chemical components in percentage by mass: 0.05-0.08% of C, 0.25-1.0% of Si, 5.0-8.0% of Mn, 16.5-19.5% of Cr, 2.5-4.5% of Ni, 0.5-2.0% of Cu, less than or equal to 0.045% of P, less than or equal to 0.0020% of S, 0.20-0.30% of N and the balance of Fe and inevitable impurities, and the bulging index FT is greater than or equal to 50 and is equal to 551-162 * (C% + N%)-9.2 * Si%-8.1 * Mn%-29 * Ni%-39 * Cu%-13.7 * Cr%. Through Mn and N alloying, the Ni content is reduced, the alloy cost is reduced, meanwhile, the bulging index FT is further controlled to be larger than or equal to 50, the ductility is larger than or equal to 55%, and the cupping value Er is larger than or equal to 11.0 mm, so that the purpose that economical high-nitrogen high-strength steel is easy to form is achieved, and the economical high-nitrogen high-strength steel is finally successfully applied to the field of products such as dish washing machine door plates and range hood covers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to austenitic stainless steel and a manufacturing method thereof, and in particular to an economical high-nitrogen easy-to-form austenitic stainless steel and a manufacturing method thereof. Background Art

[0002] Austenitic stainless steel represented by 304 has excellent corrosion resistance, processing performance and forming performance, and is widely used in the field of products, such as dishwasher door panels, range hoods, etc. However, the Ni content of 304 stainless steel is about 8%, which is relatively high, while my country is short of nickel resources, accounting for only 3.93% of the world's approximately 80 million tons of nickel metal reserves.

[0003] In recent years, two major types of nickel-saving austenitic stainless steels, namely 14% chromium content and 1% nickel content and 16% chromium content and 4% nickel content, have been industrialized at home and abroad. However, the pitting equivalent PREN (Cr+3.3Mo+30N-Mn) value is lower than 16.0, and the corrosion resistance is far inferior to 304 stainless steel (PREN value 18.5). They can only be used in dry areas and interior decoration fields, and their application scope is severely limited.

[0004] Since 2018, domestic stainless steel enterprises have adopted the design idea of ​​replacing Ni with Mn and N, such as the 304-grade corrosion-resistant high-nitrogen nickel-saving austenitic stainless steel disclosed in Chinese patent announcement number CN112501493B, whose PREN value exceeds 18.5. The product has excellent corrosion resistance and has been widely used in many fields, such as containers, prefabricated buildings, decorative welded pipes, etc. However, the yield strength of this product exceeds 400MPa, and the elongation is slightly lower, only about 50%, which can replace 304 stainless steel stamping dishwasher door panels (see Figure 1 ) and range hood (see Figure 2 ) cracking occurs at large deformation locations. Summary of the invention

[0005] The purpose of the present invention is to provide an economical high-nitrogen easy-to-form austenitic stainless steel and a manufacturing method. The stainless steel has low cost, pitting resistance reaching 304 stainless steel level, yield strength>400MPa, elongation>55%, cupping value Er>11.0mm, and pitting potential>300mV; the problem of cracking of high-nitrogen high-strength stainless steel during forming is overcome, and the stainless steel is successfully used in the field of products such as dishwasher door panels and range hood covers instead of 304 stainless steel.

[0006] To achieve the above purpose, the technical solution of the present invention is as follows:

[0007] Economical high nitrogen easy-to-form austenitic stainless steel, its chemical composition mass percentage is:

[0008] C: 0.05~0.08%,

[0009] Si: 0.25-1.0%,

[0010] Mn: 5.0~8.0%,

[0011] Cr: 16.5~19.5%,

[0012] Ni: 2.5-4.5%,

[0013] Cu: 0.5-2.0%,

[0014] P≤0.045%,

[0015] S≤0.0020%,

[0016] N: 0.20~0.30%,

[0017] The balance includes Fe and other unavoidable impurities, and the above elements must satisfy the following relationship at the same time:

[0018] Bulging index FT≥50,

[0019] FT=551-162×(C%+N%)-9.2×Si%-8.1×Mn%-29×Ni%-39×Cu%-13.7×Cr%.

[0020] Furthermore, the balance is Fe and other inevitable impurities.

[0021] Yield strength Rp of the stainless steel of the present invention 0.2 >400MPa, elongation ≥55%, cupping value Er ≥11.0mm, pitting potential >300mV.

[0022] In the composition design of the economical high nitrogen easy-to-form austenitic stainless steel of the present invention:

[0023] In order to obtain 304 grade corrosion resistant stainless steel, the Cr content of the product is controlled at 16.5-19.5%. Furthermore, since N exists in the passive film in the form of NH3, when the passive film dissolves, NH3 can combine with H + Formation of NH4 + , which increases the local pH and inhibits the further dissolution of the passive film, thereby improving the pitting corrosion resistance of the passive film. Therefore, the present invention further improves the pitting corrosion resistance of the product by N alloying, and finally obtains 304-grade corrosion-resistant stainless steel. In order to ensure that the added N can still be retained in the material during the solidification process, rather than escaping from the molten steel in the form of nitrogen, the Mn element needs to be added at the same time to increase the nitrogen solubility of the molten steel. In addition, by alloying Mn and N, it can also replace part of the Ni element, thereby saving Ni resources and reducing alloy costs.

[0024] N exists in the form of interstitial solid solution atoms in austenite, which significantly improves the yield strength of the product and slightly reduces the elongation. In order to make the steel of the present invention have excellent bulging properties on the basis of high-strength mechanical properties, the present invention studies the relationship between the bulging index FT and the content of each element. FT is a bulging property that characterizes the product. The bulging property of the material is not only related to the yield strength, but also to the work hardening ability after plastic deformation. The work hardening ability is mainly affected by the content of deformation-induced martensite. The higher the content, the stronger the work hardening ability and the better the bulging performance. The traditional use of M d30 / 50 Characterizes the ability of deformation-induced martensite, that is, the temperature at which 30% deformation produces 50% martensite. The empirical formula is: M d30 / 50= 551-462×(C%+N%)-9.2×Si%-8.1×Mn%-29×Ni%-29×Cu%-13.7×Cr%-18.5Mo%, this empirical formula is fitted based on the basic data of Cr-Ni austenitic stainless steel represented by 304. The interstitial atomic C and N content of Cr-Ni austenitic stainless steel is low (C%+N%<0.15%), and C and N cannot completely occupy the interstitial Fe atoms, resulting in insufficient austenite stability. At this time, increasing the C and N content can greatly improve the stability of austenite and significantly reduce M d30 / 50 , and sharply reduce the cupping value ( Figure 3 ).

[0025] The high nitrogen austenitic stainless steel of the present invention has a high content of C and N (C% + N% > 0.25%), and C and N atoms fully occupy the interstitial spaces of Fe atoms in the form of interstitial solid solution atoms, so the austenite stability is relatively high. At this time, increasing the C and N contents can only slightly increase the austenite stability and slightly reduce the M d30 / 50 , and slightly reduce the cupping value ( Figure 4 ). Therefore, in the steel of the present invention, M d30 / 50 It cannot be used directly to characterize the stability of high nitrogen austenite. d30 / 50 The C and N coefficients are corrected. Low C+N content Figure 3 The slope is -20.4, which is a high C+N content Figure 4 The slope is -2.85 times of 7.16, so the corresponding M d30 / 50 The C and N coefficients of the steel are reduced by 2.85 times. At the same time, considering that the steel of the present invention contains a higher Mn content, the effect of Cu in stabilizing austenite and inhibiting the formation of deformed martensite in high manganese steel is more significant than that in low manganese Cr-Ni stainless steel, so the influence coefficient of Cu content is also corrected accordingly. The corrected M d30 / 50 That is, the relationship between the bulging index FT and each alloy element is:

[0026] FT=551-162×(C%+N%)-9.2×Si%-8.1×Mn%-29×Ni%-39×Cu%-13.7×Cr%.

[0027] The influence coefficients of C and N were corrected from -462 to -162, the influence coefficient of Cu was corrected from -29 to -39, and the fitting degree R between the bulging index FT and the actual cupping value of industrialized high nitrogen austenitic stainless steel was 2 ( Figure 5 ) is 0.90, and M d30 / 50 The fitting degree R with the actual cupping value of industrialized high nitrogen austenitic stainless steel 2 Only 0.71( Figure 6 ), it can be seen that the bulging index FT fitted by the present invention is more suitable for characterizing the stability of high nitrogen austenitic stainless steel, and then characterizing the bulging performance of high nitrogen austenitic stainless steel.

[0028] In view of the above relationship, by controlling the content of each alloy element, it is found that when the bulging index FT≥50, the material elongation ≥55% and the bulging cupping value Er≥11.0mm can be achieved, which meets the performance requirements of the dishwasher door panel and range hood cover forming process.

[0029] The method for manufacturing the economical high-nitrogen easy-to-form austenitic stainless steel of the present invention comprises the following steps:

[0030] 1) Smelting and casting

[0031] According to the above composition, smelting, AOD, LF refining and continuous casting are performed to form ingots; wherein the casting temperature is controlled at 1450°C to 1500°C, preferably 1460°C to 1480°C; the cooling rate of the crystallizer is controlled at 8°C to 10°C / s, preferably 9°C to 10°C / s;

[0032] 2) Hot rolling

[0033] The heating temperature of the ingot is controlled to be 1200-1300°C, preferably 1200-1250°C; the heating time is controlled to be 180-280min, preferably 200-240min, and then the ingot is rolled to the required thickness through rough rolling and finish rolling, and then coiled, wherein the finish rolling outlet temperature, i.e., the final rolling temperature, is ≥1000°C;

[0034] 3) One annealing and one pickling

[0035] The primary annealing is carried out in an annealing furnace at a temperature of 1050-1150° C., preferably 1100-1150° C.; the annealing time is 1-10 min, preferably 3-10 min; after annealing, the steel coil is mechanically dephosphorized and finally pickled once to obtain a steel coil that meets the requirements;

[0036] 4) Cold rolling

[0037] Use conventional continuous rolling mill or reversible single rolling mill to roll to the required thickness specification;

[0038] 5) Secondary annealing and secondary pickling

[0039] The secondary annealing is carried out in an annealing furnace at a temperature of 1080-1160°C for 3-5 minutes, followed by secondary pickling.

[0040] Preferably, the first pickling in step 3) adopts a sulfuric acid section + a mixed acid section, wherein the sulfuric acid concentration in the sulfuric acid section is 250-400 g / L, preferably 300-350 g / L; the mixed acid section is nitric acid + hydrofluoric acid, the nitric acid concentration is 140-240 g / L, preferably 180-220 g / L, and the hydrofluoric acid concentration is 10-25 g / L, preferably 15-20 g / L.

[0041] Preferably, the secondary pickling in step 5) is an electrolysis + mixed acid process, the medium of the electrolysis section is Na2SO4, the electrolysis current is 3000-4000A, preferably 3500-4000A; the mixed acid section is nitric acid + hydrofluoric acid, the nitric acid concentration is 140-240g / L, preferably 180-220g / L, and the hydrofluoric acid concentration is 10-25g / L, preferably 15-20g / L.

[0042] In the method for manufacturing the economical high nitrogen easy-to-form austenitic stainless steel of the present invention:

[0043] During continuous casting, the pouring temperature is controlled at 1450℃~1500℃, preferably 1460~1480℃, which is lower than the conventional 304 steel casting temperature of 1475~1490℃. High nitrogen steel has the risk of nitrogen escaping during continuous casting. Lowering the pouring temperature is beneficial to improving the nitrogen solubility of molten steel (see Figure 7 ), reducing the risk of nitrogen escape. In addition, the cooling rate of the crystallizer is controlled to 8-10°C / s, preferably 9-10°C / s, which is much higher than the cooling rate of 6-8°C / s of conventional 304 steel. Accelerating cooling during crystallization and solidification is conducive to quickly passing through the "ferrite trap", reducing the precipitation of high-temperature ferrite, and then reducing the discharged N atoms, reducing the risk of nitrogen escape. However, the cooling rate should not be too fast, otherwise uneven cooling may cause cracks in the shell, and severe cases may even cause steel leakage accidents. Therefore, the cooling rate of the crystallizer is controlled to 8-10°C / s, preferably 9-10°C / s.

[0044] During the hot rolling process, the heating temperature is controlled at 1200-1300°C, preferably 1200-1250°C. High nitrogen steel has high strength and high deformation resistance. Compared with conventional 304 steel, the heating temperature should be set higher to soften the slab, which is conducive to smooth rolling. However, the heating temperature should not be too high, otherwise the Cu in the steel will be enriched to form liquid copper during the oxidation process, causing "copper brittleness" and causing skin defects on the surface of the steel coil. The heating time is controlled to 180-280min, preferably 200-240min, in order to fully dissolve the high-temperature ferrite phase during the solidification of the slab, while avoiding the coarse austenite structure and affecting the hot working performance. In particular, in the subsequent rolling process, it is necessary to ensure that the final rolling temperature at the end of rolling is ≥1000°C to avoid the high-viscosity oxide scale produced by too low temperature from being embedded in the steel plate surface and causing rust defects.

[0045] During the hot rolling annealing and pickling process, the annealing temperature is 1050-1150°C, preferably 1100-1150°C; the annealing time is 1-10 min, preferably 3-10 min; during the annealing and recrystallization process of high nitrogen steel, N will increase the recrystallization nucleation energy and hinder the grain growth. In order to ensure sufficient grain growth and obtain high-strength steel with good plasticity, which is conducive to cold rolling thin specifications, the annealing temperature needs to be increased as much as possible and the annealing time needs to be extended.

[0046] The hot acid pickling process preferably adopts a sulfuric acid section + mixed acid section (nitric acid + hydrofluoric acid) process, the sulfuric acid concentration in the sulfuric acid section is 250-400g / L, preferably 300-350g / L; the nitric acid concentration in the mixed acid section is 140-240g / L, preferably 180-220g / L; the hydrofluoric acid concentration is 10-25g / L, preferably 15-20g / L. The main function of the sulfuric acid section is to remove the outer layer of loose iron oxide scale, and the main function of the mixed acid section is to remove the inner layer of dense chromium oxide scale, and re-passivate to form a stable passivation film.

[0047] The annealing time in the cold pickling process is 3 to 5 minutes, which is longer than the annealing time of 304 stainless steel, which is 1 to 2 minutes. High nitrogen steel has a high yield strength, and extending the annealing time is conducive to the full recrystallization and growth of the cold-rolled broken grain structure, reducing the yield strength and improving the bulging performance. However, the annealing time should not be too long, otherwise the grain structure will be too coarse, and orange peel defects will easily appear on the surface of the product after stamping.

[0048] Beneficial effects of the present invention:

[0049] The present invention ensures that the product has excellent corrosion resistance by designing a Cr content of 16.5-19.5%, and further improves the corrosion resistance of the product by alloying with Mn and N, and finally obtains 304-grade corrosion-resistant austenitic stainless steel; at the same time, replacing part of the Ni element saves Ni resources and reduces alloy costs.

[0050] On the basis of the composition of Mn-N replacing Ni, the bulging index FT≥50 is controlled by adjusting the content of C, Si and Cu alloy elements. Combined with controlling the cold rolling annealing time of 3 to 5 minutes, the elongation can be ≥55% and the cupping value Er≥11.0mm, so that the product has excellent bulging performance on the basis of high-strength mechanical properties.

[0051] The present invention obtains a continuously cast slab with no surface defects by controlling the pouring temperature and the cooling rate of the crystallizer in the continuous casting stage; obtains a hot-rolled steel coil with no surface defects by controlling the heating temperature, heating time and final rolling temperature in the hot rolling stage; and obtains a finished stainless steel coil with high strength and excellent bulging performance by controlling the annealing temperature and annealing time in the annealing stage, which successfully replaces 304 stainless steel for use in products such as dishwasher door panels and range hood covers. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a real picture of the cracking of a dishwasher door panel stamped with high-nitrogen nickel-saving austenitic stainless steel (Chinese patent announcement number CN112501493B).

[0053] Figure 2 This is a real picture of the cracking of the range hood body stamped with high-nitrogen nickel-saving austenitic stainless steel (Chinese patent announcement number CN112501493B).

[0054] Figure 3 It is the cupping value of 304 stainless steel with different C+N contents.

[0055] Figure 4 It is the cupping value of the stainless steel of the present invention with different C+N contents.

[0056] Figure 5 It is the fitting diagram of bulging index FT and cupping value of industrialized high nitrogen austenitic stainless steel.

[0057] Figure 6 M d30 / 50 Fitting diagram with the cupping value of industrialized high nitrogen austenitic stainless steel.

[0058] Figure 7 Effect of pouring temperature on nitrogen solubility in molten steel.

[0059] Figure 8 This is a real picture of nitrogen pores on the surface of the continuous casting slab in comparative example 3.

[0060] Fig. 9 This is a physical picture of the cracked edge of the hot-rolled steel coil in comparative example 4.

[0061] Fig.10 This is the SEM image of the cracked edge of the hot-rolled steel coil in comparative example 4.

[0062] Fig.11This is a physical picture of the rust defects of the hot-rolled pickled steel coil in comparative example 4. DETAILED DESCRIPTION

[0063] The present invention will be further described below in conjunction with the embodiments and drawings.

[0064] The compositions of the embodiments and comparative examples of the present invention are shown in Table 1, and the balance includes Fe and other inevitable impurities; the manufacturing processes and properties of the embodiments and comparative examples are shown in Table 2 and Table 3, respectively.

[0065] The tensile properties test of the material is carried out according to GB / T 228.1 "Tensile test of metallic materials Part 1: Room temperature test method".

[0066] The pitting potential test was carried out in accordance with GB / T 17899-1999 “Method for measuring pitting potential of stainless steel”. The test solution was 3.5% NaCl solution and the test temperature was 30±1°C.

[0067] The bulging performance cupping value Er test is carried out in accordance with GB / T 4156-2007 "Erichsen cupping test for metal sheets and strips".

[0068] The Ni content in Comparative Example 1 exceeds the upper limit of the constraint of the present invention, resulting in a bulging index FT of only 32.7, which is lower than 50. The content of deformed martensite is reduced during the stamping process, and the work hardening ability is reduced, resulting in an elongation of 50.8%, which is lower than 55%. The bulging cupping value Er is 10.62 mm, which does not reach above 11.0 mm, and the stamped dishwasher door panel cracks.

[0069] In Comparative Example 2, the contents of each element are within the control range, and the bulging index FT>50, but the cold rolling annealing time is insufficient, which is only 1.6min, which is not within the control range of 3-5min of the present invention, and the grains are not fully grown, resulting in the yield strength Rp of the material. 0.2 The elongation is too high and the expansion cup value Er is 10.56mm, which does not reach above 11.0mm. The stamped dishwasher door panel also cracks.

[0070] In Comparative Example 3, the continuous casting temperature was 1505°C, which was beyond the control range of 1450-1500°C of the present invention; the cooling rate of the crystallizer was 7.6°C / s, which was beyond the control range of 8-10°C / s of the present invention. Nitrogen escape occurred during the continuous casting process, and pores appeared on the surface of the continuous casting slab ( Figure 8 ).

[0071] In comparative example 4, the heating time is 175 min, which is beyond the control range of the present invention of 180 to 280 min, and the hot-rolled steel coil has cracked edges ( Fig. 9 ). Sampling analysis at the crack edge revealed a large number of strip-shaped precipitation phases near the crack ( Fig.10), according to the electron probe micro-area composition analysis, the Cr element in the precipitation phase 1, precipitation phase 2, and precipitation phase 3 is as high as more than 30%, which is much higher than the content of about 18% in the austenite matrix; the content of Mn and Ni is 3.2% and 1.2% respectively, which is much lower than the content of 6.3% and 2.92% in the austenite matrix. The precipitation phase is judged to be ferrite. Due to the short heating time, the residual ferrite in the ingot is not completely dissolved, resulting in cracks formed at the interface between the two phases during rolling, and eventually crack edge defects.

[0072] In addition, the final rolling temperature in Comparative Example 4 was 906°C, which did not reach the process requirement of 1000°C or above, resulting in the high viscosity oxide scale formed at low temperature being embedded in the surface of the steel plate, which was difficult to remove by pickling and eventually formed rust defects on the surface of the steel strip ( Fig.11 ).

[0073] Tables 1 to 3 also list the composition of comparative example 5 (Chinese patent CN112501493B) and the bulging index FT fitted according to the present invention, the value of which is 34, far below 50, and the work hardening ability is insufficient; and the secondary annealing time is 2 minutes, the grains are not fully grown, resulting in a high yield strength of 446MPa and a low elongation of 52.1%. It can be predicted that this comparative patent steel will crack during the stamping process of the dishwasher door panel.

[0074] In addition, Tables 1 to 3 also list the typical composition and bulging index FT of 304 stainless steel, which is 65.6, higher than 50, and has good work hardening ability. Although its cold rolling annealing time is short, only 1.5 minutes, due to the low N content and low yield strength in 304 stainless steel, its cupping value is still as high as 12.4mm, which is fully capable of meeting the bulging performance requirements of forming dishwasher door panels.

[0075] Examples 1-10 are all controlled in accordance with the composition design, composition constraints and processing technology of the present invention, so that the products not only have high-strength mechanical properties, but also have excellent bulging properties and corrosion resistance, thereby realizing the application of economical high-nitrogen austenitic stainless steel in products such as dishwasher door panels and range hood covers.

[0076]

[0077]

[0078]

[0079]

Claims

1. Economical high nitrogen easy-to-form austenitic stainless steel, its chemical composition mass percentage is as follows: C:0.05~0.08%, Si: 0.25-1.0%, Mn: 5.0~8.0%, Cr:16.5~19.5%, Ni: 2.5-4.5%, Cu: 0.5-2.0%, P≤0.045%, S≤0.0020%, N:0.20~0.30%, The balance includes Fe and other unavoidable impurities, and the above elements must satisfy the following relationship at the same time: Bulging index FT≥50, FT=551-162×(C%+N%)-9.2×Si%-8.1×Mn%-29×Ni%-39×Cu%-13.7×Cr%.

2. The economical high nitrogen easy-to-form austenitic stainless steel as claimed in claim 1, characterized in that: The balance is Fe and other inevitable impurities.

3. The economical high nitrogen easy-to-form austenitic stainless steel according to claim 1 or 2, characterized in that: The yield strength Rp of the stainless steel 0.2 >400MPa, elongation ≥55%, cupping value Er ≥11.0mm, pitting potential >300mV.

4. The method for producing economical high nitrogen easy-to-form austenitic stainless steel according to any one of claims 1 to 3, characterized in that: The steps include: 1) Smelting and casting Smelting, AOD, LF refining and continuous casting into ingots according to claim 1 or 2; Wherein, the casting temperature is controlled at 1450°C to 1500°C, preferably at 1460°C to 1480°C; The cooling rate of the crystallizer is controlled at 8-10°C / s, preferably 9-10°C / s; 2) Hot rolling The heating temperature of the ingot is controlled to be 1200-1300°C, preferably 1200-1250°C; the heating time is controlled to be 180-280min, preferably 200-240min, and then the ingot is rolled to the required thickness through rough rolling and finish rolling, and then coiled, wherein the finish rolling outlet temperature, i.e., the final rolling temperature, is ≥1000°C; 3) One annealing and one pickling The primary annealing is carried out in an annealing furnace at a temperature of 1050-1150° C., preferably 1100-1150° C.; the annealing time is 1-10 min, preferably 3-10 min; after annealing, the steel coil is mechanically dephosphorized and finally pickled once to obtain a steel coil that meets the requirements; 4) Cold rolling Use conventional continuous rolling mill or reversible single rolling mill to roll to the required thickness specification; 5) Secondary annealing and secondary pickling The secondary annealing is carried out in an annealing furnace at a temperature of 1080-1160°C for 3-5 minutes, followed by secondary pickling.

5. The economical high nitrogen easy-to-form austenitic stainless steel manufacturing method as claimed in claim 4, characterized in that: Step 3) The primary pickling adopts a sulfuric acid section + a mixed acid section, wherein the sulfuric acid concentration in the sulfuric acid section is 250-400 g / L, preferably 300-350 g / L; the mixed acid section is nitric acid + hydrofluoric acid, the nitric acid concentration is 140-240 g / L, preferably 180-220 g / L, and the hydrofluoric acid concentration is 10-25 g / L, preferably 15-20 g / L.

6. The economical high nitrogen easy-to-form austenitic stainless steel manufacturing method as claimed in claim 4, characterized in that: Step 5) The secondary pickling is an electrolysis + mixed acid process, the electrolysis medium is Na2SO4, the electrolysis current is 3000-4000A, preferably 3500-4000A; the mixed acid section is nitric acid + hydrofluoric acid, the nitric acid concentration is 140-240g / L, preferably 180-220g / L, and the hydrofluoric acid concentration is 10-25g / L, preferably 15-20g / L.

Citation Information

Patent Citations

  • Ni-saving austenitic stainless steel cold-rolled sheet with excellent processability and manufacturing method thereof

    CN102605291A

  • High-forming nitrogen-containing austenitic stainless steel and manufacturing method thereof

    CN108690939A

  • Nickel-saving high-nitrogen austenitic stainless steel with excellent pitting corrosion resistance and sulfuric acid corrosion resistance and manufacturing method

    CN112501493A

  • Corrosion resistant austenitic stainless steel with improved galling resistance

    US5340534A

  • Method for producing thin sheet from a stainless austenitic crmnni steel

    WO2016177473A1

Cited By

  • High-strength austenitic stainless steel with yield strength of 420 MPa

    CN120536836A

  • Austenite stainless steel including copper

    EP4796666A1